2004
DOI: 10.1002/ls.3010170102
|View full text |Cite
|
Sign up to set email alerts
|

Lubricant oils additivated with polymers in EHD contacts: Part 1. Rheological behaviour

Abstract: This paper reports on the influence of a polymer additive on the traction behaviour of a mineral oil investigated using a twodisc machine at different temperatures and contact pressures. A semi-empirical approach was used for determining the effective lubricant rheological parameters -the elasiic shear modulus, the viscosity of the lubricant, and the 1im.iting and Eyring stresses -in elastohydrodynamic contacts. Using this approach, the effect of polymer concentration on the rheological parameters that appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
2
5
0
1
Order By: Relevance
“…Several authors 22,23 report constant ratios between the reference stress and the limiting shear stress obtained experimentally, while others such as Bair and Winer 24 conclude analytically that τE2·Λ/α which agrees well with the experimental values from Johnson and Tevaarwerk. 19 Their result explained the sigmoid shape of the friction curve by the growth of the plastic region within the contact ruled by the limiting shear stress.…”
Section: Partial Ehl Friction Coefficient Modelsupporting
confidence: 69%
“…Several authors 22,23 report constant ratios between the reference stress and the limiting shear stress obtained experimentally, while others such as Bair and Winer 24 conclude analytically that τE2·Λ/α which agrees well with the experimental values from Johnson and Tevaarwerk. 19 Their result explained the sigmoid shape of the friction curve by the growth of the plastic region within the contact ruled by the limiting shear stress.…”
Section: Partial Ehl Friction Coefficient Modelsupporting
confidence: 69%
“…The present paper continues the previous investigations, [6][7][8][9][10][11] being focused on friction behaviour in a tapered rolling bearing.…”
Section: Introductionsupporting
confidence: 69%
“…The samples were pre-sheared before testing, and the values of the viscosity were obtained after stabilization of the shear stress. 9,11 Figure 1 presents the fl ow curves obtained for base oil and samples of base oil containing polymers at 50°C. For the investigated samples, at shear rates lower than 300 s −1 , it is observed that the viscosity increases with increasing the polymer concentration up to 1.5% PE, whereas for 2% PE the viscosity decreases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations